Chemical content of agarwood-producing trees from Buru Island, Maluku, Indonesia - NINGSIE INDAHSUARY UAR; LINA KARLINASARI; ISKANDAR Z. SIREGAR; SETYO PERTIWI (Society for Indonesian Biodiversity, 2024)
Abstract. Uar NI, Karlinasari L, Siregar IZ, Pertiwi S. 2024. Chemical content of agarwood-producing trees from Buru Island, Maluku, Indonesia. Biodiversitas 25: 2629-2636. Agarwood or gaharu is a plant that grows abundantly and naturally throughout almost all of Indonesia, including Buru Island and Moluccas. The exploration of agarwood-producing plants has been motivated by the superior quality of agarwood, which is closely linked to its chemical composition. This study aimed to determine the chemical components and resin contents of cultivated and natural agarwood-producing trees on Buru Island. The research was carried out in three areas, considered the centers of agarwood production on Buru Island: Airbuaya, Fenaleisela, and Batabual. The identification of tree species was carried out as an initial stage to identify the tree species that produce agarwood. The quality of agarwood was determined by reference to the Indonesian standard, resin content analysis, and chemical component identification results evaluated through GC-MS laboratory testing. The results showed that agarwood-forming compounds were present in cultivated and natural plants. Aquilaria filaria is the agarwood-producing tree found at the research location. The chemical components of agarwood from three locations contained sesquiterpene alcohol, chromone, and acid compounds, with the resin content in natural forests showing higher values than in cultivated plants. The quality of agarwood depends on its constituent compounds and chemical content. Based on the research results, the agarwood plants on Buru Island, a testament to the richness of Indonesia's natural resources, have the potential to be developed to a greater extent so that, with good management, they can contribute significantly to the development of local communities.